SOCIAL JUSTICE FOR VULNERABLE CHILDREN: THE JURY/HAPPY CHILD PROJECT IN TOCANTINS - Cosobeck da Costa, Bernardino (2024)
This is a case study based on the analysis of several criminal proceedings within the competence of the Jury Court of the Comarca of Wanderlândia, Goiatins, Itaguatins and Colinas do Tocantins/TO, having as object the Project Jury/Happy Child as a good practice in the Judiciary, developed by the Magistrate, José Carlos Ferreira Machado, where surplus food from the Jury Sessions is destined for public schools and entities that welcome children in food vulnerability. This research registers the existence of the objectification of the human being in contemporary society and how the Judiciary, through good practices, can give effect to Social Justice by providing food reinforcement for children in food vulnerability, in addition to promoting lectures on the role of the judiciary and institutions. The meaning of this article is to investigate the potential of the Judiciary to promote the dignity of the human person through surplus resources and availability through the Magistrate for the concreteness of the social project in question, hence it starts with theorists such as Giorgio Agamben, Michael Foucault, dente others, in order to seek to understand this practice employed in the Judiciary of the State of Tocantins.